TIGIT Signaling Pathway Regulates Natural Killer Cell Function in Chronic Hepatitis B Virus Infection - Wang, Juan; Hou, Hongyan; Mao, Lie; Wang, Feng; Yu, Jing; Luo, Ying; Lin, Qun; Sun, Ziyong (Frontiers in Medicine, 2022)
Background and Objective Persistent infection of hepatitis B virus (HBV) and liver damage in immune active chronic hepatitis B (CHB) could be partly due to the overreaction of natural killer (NK) cells, including pro-inflammatory cytokine secretion and cytotoxicity. An immunosuppressive receptor, T-cell immunoglobulin and immunoreceptor tyrosine–based inhibitory motif (ITIM) domain (TIGIT) is specifically expressed in NK cells. This study aims to investigate the role of the TIGIT signaling pathway in regulating NK cell functions in patients with CHB. Method We comparatively assessed the expression of TIGIT in NK cells of patients with immune active CHB (CHB-IA), carriers of immune control chronic HBV (CHB-IC), and healthy controls (HCs), and then explored mechanisms of the TIGIT signaling pathway in regulating NK cell-mediated liver injury by different molecular assessments. Result The expression of TIGIT in NK cells was enhanced in CHB-IC but was reduced in CHB-IA compared with the HC group. In patients with CHB-IA, the expression of TIGIT was inversely correlated with intensity of the liver damage. Moreover, TIGIT-NK cells show higher IFN-γ secretion capability, degranulation activity, and cytotoxicity but lower apoptosis than TIGIT+ NK cells. Blockade of the TIGIT pathway with anti-TIGIT antibody increased NK cell function, while activation of the TIGIT pathway with TIGIT Fc and CD155 Fc chimera protein down-regulated NK cell function. Conclusion Our data showed that the TIGIT signaling pathway participates in NK cell impairment, which could be used as a new therapeutic target to protect patients with chronic HBV infection from severe liver injury.